Proses Perencanaan Anggaran pada Usaha Kuliner “Seblak” - Aziz Fajar Saputro; Redika Fajar Cahyono; Farhan As Sidiq; Rizal Fakihan; Muhammad Aditya Juliyanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
A company budget is a structured and logical plan. In business management, a budget serves as a planning, control, and decision-making tool, enabling the company to achieve effective and efficient goals. Furthermore, a company budget aims to regulate cash flow, preventing waste. This article discusses the budgeting process in the culinary business